Effect of oocyte vitrification on DNA damage in metaphase II oocytes and the resulting preimplantation embryos. Issue 11 (13th August 2019) - Chang, Haoya; Chen, Huanhuan; Zhang, Lei; Wang, Yile; Xie, Xiaogang; Zhang, Yong; Quan, Fusheng
Abstract: As an assisted reproduction technology, vitrification has been widely used for oocyte and embryo cryopreservation. Many studies have indicated that vitrification affects ultrastructure, gene expression, and epigenetic status. However, it is still controversial whether oocyte vitrification could induce DNA damage in metaphase II (MII) oocytes and the resulting early embryos. This study determined whether mouse oocytes vitrification induce DNA damage in MII oocytes and the resulting preimplantation embryos, and causes for vitrification‐induced DNA damage. The effects of oocyte vitrification on reactive oxygen species (ROS) levels, γ‐H2AX accumulation, apoptosis, early embryonic development, and the expression of DNA damage‐related genes in early embryos derived by in vitro fertilization were examined. The results indicated that vitrification significantly increased the number of γ‐H2AX foci in zygotes and two‐cell embryos. Trp53bp1 was upregulated in zygotes, two‐cell embryos and four‐cell embryos in the vitrified group, and Brca1 was increased in two‐cell embryos after vitrification. Vitrification also increased the ROS levels in MII oocytes, zygotes, and two‐cell embryos and the apoptotic rate in blastocysts. Resveratrol (3, 5, 4′‐trihydroxystilbene) treatment decreased the ROS levels and the accumulation of γ‐H2AX foci in zygotes and two‐cell embryos and the apoptotic rate in blastocysts after vitrification. Overall, vitrification‐induced abnormal ROS generation, γ‐H2AX accumulation, an increase in the apoptotic rate and the disruption of early embryonic development. Resveratrol treatment could decrease ROS levels, γ‐H2AX accumulation, and the apoptotic rate and improve early embryonic development. Vitrification‐associated γ‐H2AX accumulation is at least partially due to abnormal ROS generation. Abstract : Vitrification‐induced DNA double‐strand breaks in zygotes and two‐cell embryos. Vitrification‐induced abnormal reactive oxygen species (ROS) generation. Resveratrol treatment decreased the ROS levels and reduced the accumulation of γ‐H2AX foci in zygotes and two‐cell embryos after vitrification.